Health-related quality of life in patients waiting for major joint replacement. A comparison between patients and population controls - Hirvonen, Johanna (BioMed Central, 2006)
BACKGROUND: Several quality-of-life studies in patients awaiting major joint replacement have focused on the outcomes of surgery. Interest in examining patients on the elective waiting list has increased since the beginning of 2000. We assessed health-related quality of life (HRQoL) in patients waiting for total hip (THR) or knee (TKR) replacement in three Finnish hospitals, and compared patients' HRQoL with that of population controls. METHODS: A total of 133 patients awaiting major joint replacement due to osteoarthritis (OA) of the hip or knee joint were prospectively followed from the time the patient was placed on the waiting list to hospital admission. A sample of controls matched by age, gender, housing and home municipality was drawn from the computerised population register. HRQoL was measured by the generic 15D instrument. Differences between patients and the population controls were tested by the independent samples t-test and between the measurement points by the paired samples t-test. A linear regression model was used to explain the variance in the 15D score at admission. RESULTS: At baseline, 15D scores were significantly different between patients and the population controls. Compared with the population controls, patients were worse off on the dimensions of moving (P < 0.001), sleeping (P < 0.001), sexual activity (P < 0.001), vitality (P < 0.001), usual activities (P < 0.001) and discomfort and symptoms (P < 0.001). Further, psychological factors – depression (P < 0.001) and distress (P = 0.004) – were worse among patients than population controls. The patients showed statistically significantly improved average scores at admission on the dimensions of moving (P = 0.026), sleeping (P = 0.004) and discomfort and symptoms (P = 0.041), but not in the overall 15D score compared with the baseline. In patients, 15D score at baseline (P < 0.001) and body mass index (BMI) (P = 0.020) had an independent effect on patients' 15D score at hospital admission. CONCLUSION: Although patients' HRQoL did not deteriorate while waiting, a consistently worse HRQoL was observed in patients waiting for major joint replacement compared with population controls.